Circulating Apelin-17 and Elabela Levels as Predictive Biomarkers of Neurodegeneration and Cognitive Decline in Alzheimer’s Disease - Shaimaa Imad Ali; Alabbas Majeed (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Background: Alzheimer’s disease is characterized by progressive neurodegeneration and cognitive decline. Early diagnosis and monitoring are critical but remain challenging. Apelin-17 and Elabela, endogenous ligands of the apelin receptor (APJ), have emerged as neuroprotective peptides with potential biomarker utility. Objective: To evaluate circulating Apelin-17 and Elabela levels as predictive biomarkers of neurodegeneration and cognitive impairment in Alzheimer’s disease. Methods: We measured plasma Apelin-17 and Elabela in 60 Alzheimer’s disease patients and 60 cognitively normal controls. Correlations with cognitive scores, CSF AD biomarkers (Aβ42, total tau, phosphorylated tau), inflammatory markers (IL-6, TNF-α, CRP), and MRI volumetric data were assessed. A subset (n=30) was followed longitudinally for 12 months. Results: Alzheimer’s disease patients showed significantly reduced Apelin-17 (48.7 ± 15.3 pg/mL vs. 82.1 ± 20.4 pg/mL) and Elabela levels (31.5 ± 9.8 pg/mL vs. 57.3 ± 14.1 pg/mL; p < 0.001 for both). Peptide levels correlated positively with MMSE and specific cognitive domains and inversely with CSF tau, inflammatory markers, and brain atrophy (hippocampus, entorhinal, parietal cortex). Baseline peptides predicted 12-month cognitive decline and hippocampal volume loss. Combined biomarker models including Apelin-17, Elabela, and classical markers improved diagnostic accuracy (AUC=0.93). Conclusion: Circulating Apelin-17 and Elabela are promising predictive biomarkers for neurodegeneration and cognitive decline in Alzheimer’s disease, reflecting multiple pathological processes. They hold potential for early diagnosis, monitoring, and therapeutic targeting.